2017
DOI: 10.1007/s40211-017-0223-4
|View full text |Cite
|
Sign up to set email alerts
|

Sexual abuse of minors within the Catholic Church and other institutions

Abstract: Sexual violence against children remains a global public health problem. The health sector has an opportunity and responsibility to be part of the multisector collaboration to prevent and respond to sexual abuse of minors. The following article presents a critical analysis of hitherto published empirical studies that examine the extent and variety of sexual abuse of minors within the Catholic Church and other institutions. The analysis consists of 40 studies concerning the Catholic Church and 13 studies concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
1
4
0
6
Order By: Relevance
“…Our study also shows comparable results concerning the characteristics of the victims. While females were more frequently victimized in other circumstances (Bolen & Scannapieco, 1999), all studies point toward a higher share of male victims in the context of sexual abuse of minors in the Catholic Church (Dressing, Dölling, Hermann, Horten, Kruse, et al, 2017). In the German sample, 62% of persons affected by sexual abuse were male.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study also shows comparable results concerning the characteristics of the victims. While females were more frequently victimized in other circumstances (Bolen & Scannapieco, 1999), all studies point toward a higher share of male victims in the context of sexual abuse of minors in the Catholic Church (Dressing, Dölling, Hermann, Horten, Kruse, et al, 2017). In the German sample, 62% of persons affected by sexual abuse were male.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Australia reported an even higher prevalence of accused Catholic Priests at 7.0% (Royal Commission into Institutional Responses to Child Sexual Abuse, 2017). So far, European studies have only reported absolute numbers of accused clerics (Dressing, Dölling, Hermann, Horten, Kruse, et al, 2017). A Dutch study (Deetman et al, 2011) reported 800 accused clerics and ecclesiastical staff and 774 victims.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Weiterhin liegt eine systematische Literaturübersicht vor, deren Ziel es war, einen Überblick über die bisherigen empirischen Befunde zum sexuellen Missbrauch an Kindern und Jugendlichen im institutionellen Kontext, insbesondere in der katholischen Kirche, zu gewinnen [16].…”
Section: Methodikunclassified
“…B. in Schulen, Sportvereinen oder im Verantwortungsbereich von Kirchen [1]. Bezüglich des sexuellen Missbrauchs von Minderjährigen im institutionellen Kontext finden sich insbesondere Studien zur katholischen Kirche, andere Institutionen sind bisher weniger gründlich untersucht worden [2]. Das Ausmaß des sexuellen Missbrauchs von Kindern in der katholischen Kirche Deutschlands wurde im Rahmen der von der Deutschen Bischofskonferenz ausgeschriebenen Studie "Sexueller Missbrauch an Minderjährigen durch katholische Priester, Diakone und männliche Ordensangehörige im Bereich der Deutschen Bischofskonferenz" untersucht, die entsprechend der beteiligten Forschungsinstitute aus Mannheim, Heidelberg und Gießen das Akronym MHG-Studie trägt.…”
Section: Introductionunclassified